Global Phenomenon: The Millennial Generation is Trapped by Sandwich Generation in Indonesia - Wahyu Trisno Aji; Faizah harani (MultiTech Publisher, 2023)
This study is a theoretical exploration of the global phenomenon related to the millennial generation trapped in the sandwich generation. The term sandwich generation, was first introduced by Dorothy Miller in her paper entitled